Application of a novel index for understanding vascular health following pharmacological intervention in a pre-clinical model of metabolic disease - Menon, Nithin J.; Halvorson, Brayden D.; Alimorad, Gabrielle H.; Frisbee, Jefferson C.; Lizotte, Daniel J.; Ward, Aaron D.; Goldman, Daniel; Chantler, Paul D.; Frisbee, Stephanie J. (Frontiers in Pharmacology, 2023)
While a thorough understanding of microvascular function in health and how it becomes compromised with progression of disease risk is critical for developing effective therapeutic interventions, our ability to accurately assess the beneficial impact of pharmacological interventions to improve outcomes is vital. Here we introduce a novel Vascular Health Index (VHI) that allows for simultaneous assessment of changes to vascular reactivity/endothelial function, vascular wall mechanics and microvessel density within cerebral and skeletal muscle vascular networks with progression of metabolic disease in obese Zucker rats (OZR); under control conditions and following pharmacological interventions of clinical relevance. Outcomes are compared to “healthy” conditions in lean Zucker rats. We detail the calculation of VHI, full assessments of validity, and describe progressive changes to VHI over the development of metabolic disease in OZR. Further, we detail the improvement to cerebral and skeletal muscle VHI following chronic treatment of OZR with anti-hypertensive (15-52% for skeletal muscle VHI; 12-48% for cerebral VHI; p<0.05 for both), anti-dyslipidemic (13-48% for skeletal muscle VHI; p<0.05), anti-diabetic (12-32% for cerebral VHI; p<0.05) and anti-oxidant/inflammation (41-64% for skeletal muscle VHI; 29-42% for cerebral VHI; p<0.05 for both) drugs. The results present the effectiveness of mechanistically diverse interventions to improve cerebral or skeletal muscle VHI in OZR and provide insight into the superiority of some pharmacological agents despite similar effectiveness in terms of impact on intended targets. In addition, we demonstrate the utility of including a wider, more integrative approach to the study of microvasculopathy under settings of elevated disease risk and following pharmacological intervention. A major benefit of integrating VHI is an increased understanding of the development, timing and efficacy of interventions through greater insight into integrated microvascular function in combination with individual, higher resolution metrics.